Kajian Kebijakan Publik Pada Masa Khalifah Umar Bin Abdul Azis dan Relevansinya dengan Kebijakan Publik Pemerintah Indonesia Saat ini (Perspektif Pengangguran dan Pengentasan Kemiskinan) - Setiyanto Priyonggo; Lucky Nugroho; Zulfahmi Zulfahmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to determine the current level of unemployment and poverty in Indonesia and the public policies that can be implemented as a solution to these problems. The method used is descriptive qualitative research which aims to provide an overview or explanation related to the problem formulation. The results of this research are (i) The Indonesian government can implement public policies that support the utilization of the potential of the agricultural sector and existing agricultural land to improve community welfare, create jobs and reduce unemployment rates as was implemented during the time of the Caliph Umat bin Abdul Aziz. (ii) The Indonesian government can implement public policies based on the principles of good zakat and tax governance that were implemented during the time of Caliph Umar bin Abdul Aziz. The implications of this research provide information regarding the comparison of unemployment rates and poverty rates in Indonesia with other countries in the world and also during the time of Caliph Umar bin Abdul Aziz. Therefore, the latest in this research is related to the relevance of public policy during the government of Caliph Umar bin Abdul Aziz in order to reduce unemployment and alleviate poverty with the current public policy of the Indonesian government.